Leadership Orientation of Afghan and Japanese Respondents: A Study of â€œGuzaaraâ€ or Getting Along in Asia - Mujtaba, Bahaudin G. (Information Management and Business Review, 2019)
The purpose of this paper is to analyze the leadership tendencies of Afghan and Japanese respondents by exploring their task and relationship orientations. While there are many published studies on the Japanese work culture and leadership practices, research about Afghan working adults is limited. Using the Style Questionnaire, this research collected and compared the leadership orientations of 400 respondents from each country based on national culture on the task and relationship-orientation continuums. To deepen the understanding of Afghan leadership tendencies, we explore their culture of â€œguzaaraâ€ (getting along) practices. Similarly, we discuss the Japanese concept of â€œbaâ€ (interactive knowledge creation) as one example of a best practice that can be benchmarked by others in society. Both Afghanistan and Japan are high-context cultures; therefore, people are expected to be more relationship-oriented. While respondents from both countries do have a stronger focus on their relationships, data shows that Afghans have a significantly higher score on both the task-orientation as well as relationship-orientation continuums, compared to their Japanese counterparts. Implications, recommendations and limitations of the study are provided. The findings that Japanese and Afghan employees are indeed focused on their relationships, and that they have a moderately high task orientation scores, are useful for managers and expatriates working in these two Asian countries.